The Management and Leaderhip of Non-Governmental Organizations in Sabah - Siti Noor Fazariah Bt Suis @ Mohd Rusdy; Adi Fahrudin (Asian Social Work Journal, 2017)
This is a concept paper on the management and leadership of Non-Governmental Organizations (NGOs). Literature reviews from previous studies were discussed in giving a thorough understanding on the management process and the leadership practised by the NGO’s leaders in their stands of their clients. The discussion on literature reviews includes the management and leadership trend of some NGO’s in Malaysia and then highlighting some major issues and challenges faced by that NGO’s and provides some strategies in terms of the management and leadership process in responding toward client’s right and the development of the non-governmental organizations.